2012
DOI: 10.1136/thoraxjnl-2012-202003
|View full text |Cite
|
Sign up to set email alerts
|

IL-25 drives remodelling in allergic airways disease induced by house dust mite

Abstract: BackgroundOverexpression of the transforming growth factor β family signalling molecule smad2 in the airway epithelium provokes enhanced allergen-induced airway remodelling in mice, concomitant with elevated levels of interleukin (IL)-25.ObjectiveWe investigated whether IL-25 plays an active role in driving this airway remodelling.MethodsAnti-IL-25 antibody was given to mice exposed to either inhaled house dust mite (HDM) alone, or in conjunction with an adenoviral smad2 vector which promotes an enhanced remod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(170 citation statements)
references
References 31 publications
8
155
1
6
Order By: Relevance
“…Using a house dust mite allergen stimulation model in adult mice, and with the coadministration of an adenoviral vector expressing Smad2 to enhance a remodelling phenotype, Gregory and colleagues reported that anti-IL-25 abrogated peribronchial collagen deposition and airway hyperreactivity (62). This correlated with a moderate reduction of TRANSATLANTIC AIRWAY CONFERENCE IL-5 and IL-13 and a more profound decrease in IL-33 and TSLP.…”
Section: Ilc2 In Lung Allergy and Inflammationmentioning
confidence: 90%
“…Using a house dust mite allergen stimulation model in adult mice, and with the coadministration of an adenoviral vector expressing Smad2 to enhance a remodelling phenotype, Gregory and colleagues reported that anti-IL-25 abrogated peribronchial collagen deposition and airway hyperreactivity (62). This correlated with a moderate reduction of TRANSATLANTIC AIRWAY CONFERENCE IL-5 and IL-13 and a more profound decrease in IL-33 and TSLP.…”
Section: Ilc2 In Lung Allergy and Inflammationmentioning
confidence: 90%
“…157 Moreover, blocking IL-17E in the airways of allergenFunctional mechanisms of IL-17 family cytokines X Song et al challenged mice decreases the deposition of peribronchial collagen and the hyperplasia of airway smooth muscles. 158 IL-17E contributes to allergenic resources by orchestrating airway remodelling in addition to inducing airway type 2 inflammation. Thus, IL-17B shows opposing phenotypes to IL-17E during allergic asthma.…”
Section: Il-17dmentioning
confidence: 99%
“…Our data showed that both IL-25 and OVAchallenged mice showed increased production of both mediators, first in the lung parenchyma and in the airways lumen, with a time course reflecting that of elevated blood vessel signature markers including vWF and ERG. vWF is a common marker for evaluating angiogenesis in vivo and ex vivo [12], while ERG is a member of the ETS (erythroblast transformation-specific) family of transcription factors which is selectively expressed by endothelial cells, specific haematopoetic cells and pre-cartilage cells. It has been shown that ERG plays an important role in blood vessel homeostasis and angiogenesis by regulating a variety of endothelial cellular functions including survival, junctional stability and migration [26].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, overexpression or exogenous administration of IL-25 produces an asthma-like inflammatory response, including increased serum IgE production, blood eosinophilia and lung eosinophilic infiltrates, epithelial cell hyperplasia/hypertrophy, increased mucus secretion and airways hyperreactivity [8][9][10][11]. Conversely, blockade of IL-25 remarkably reduced Th2 cytokine production and airways inflammation [7,12], and in addition ameliorated airways remodelling changes including peribronchial collagen deposition and smooth muscle hyperplasia, with corresponding reduction of hyperreactivity [12].…”
Section: Introductionmentioning
confidence: 99%